01.11 Resident non-classical monocytes are critically important for tissue destruction in arthritis. (1st March 2017) - Puchner, Antonia; Saferding, Victoria; Bonelli, Michael; Mikami, Yohei; Goncalves-Alves, Eliana; Binder, Nikolaus B; Steiner, Carl-Walter; Hayer, Silvia; Niederreiter, Birgit; Koenders, Marije M; Smolen, Josef S; Redlich, Kurt; et al.
Abstract : Background: Bone destruction in rheumatoid arthritis is mediated by osteoclasts, which are derived from precursor cells of the myeloid lineage. Although there is much known about mature osteoclasts, the identity of osteoclast precursor populations during arthritis is poorly understood. Blood monocytes can be subdivided in classical inflammatory monocytes (CD115 + Ly6C high CCR2 + ) and non-classical resident monocytes (CD115 + Ly6C -/low CCR2 - ) and especially classical monocytes have been implicated in mediating tissue damage in autoimmunity. Methods: HTNFtg mice were clinically scored once per week for grip strength and swelling. In addition, blood was collected every other week starting on week 4. Mice were sacrificed at week 10 - blood, spleen and bone marrow were collected for flow cytometry analysis. K/BxN Arthritis was induced in wild type mice, blood and spleen were collected 14 days after disease induction. HTNFtg/CCR2 -/- and hTNFtg mice were analysed histologically. Different monocyte subsets were Facs-sorted and cultured in the presence of RANKL and MCSF to induce osteoclasts. RNA sequencing of RANKL stimulated osteoclast precursor cells was performed. Here we show that hTNFtg mice lacking CCR2, which lack circulating classical inflammatory monocytes, show enhanced local bone erosion and osteoclast generation in chronic TNF driven arthritis. When we correlated the number of the two monocyte subsets in blood with histological signs of joint destruction the number of inflammatory monocytes did not correlate at all with those parameters. In contrast, the number of non-classical monocytes in blood significantly correlated with the extent of tissue damage in both hTNFtg arthritis and also K/BxN serum transfer arthritis. Histological examination revealed that while all infiltrating monocytes express CD115, only a small fraction of these cells express Ly6C, suggesting that the synovial infiltrate predominantly consists of Ly6C -/low monocytes. Upon sorting resident and from blood, we demonstrate that resident Ly6C -/low monocytes are more potent to form osteoclasts ex vivo than classical Ly6C high monocytes. Genome-wide transcriptome profiling revealed increased expression of genes which are required for pre-osteoclast fusion in RANKL-stimulated resident Ly6C -/low monocytes. Conclusion: Non classical resident monocytes possess particular osteoclastogenic potential and their numbers in blood correlate with histological parameters of joint destruction in two different models of inflammatory arthritis. Therefore these cells may provide a biomarker for erosive inflammatory arthritis and even a possible target for therapeutically intervention.